Intergenerational education mobility and the level of development: Evidence from Turkey - Abdurrahman Bekir Aydemir; Hakkı Yazıcı (Koç University-TÜSİAD Economic Research Forum (ERF), 2017)
This paper empirically investigates whether emigrants from MENA countries self-select on cultural traits such as religiosity and gender-egalitarian attitudes. To do so, we use Gallup World Poll data on individual opinions and beliefs, migration aspirations, short-run migration plans, and preferred destination choices. We find that individuals who intend to emigrate to OECD, high-income countries exhibit significantly lower levels of religiosity than the rest of the population. They also share more gender-egalitarian views, although the effect only holds among the young (aged 15 to 30), among single women, and in countries with a Sunni minority. For countries mostly affected by Arab Spring, since 2011 the degree of cultural selection has decreased. Nevertheless, the aggregate effects of cultural selection should not be overestimated. Overall, self-selection along cultural traits has limited (albeit non negligible) effects on the average characteristics of the population left behind, and on the cultural distance between natives and immigrants in the OECD countries.
Keywords: J6; I2; R0; 330; intergenerational mobility; education; economic development; three generations